Rokat Pandhaba Tradition as a Local Legal System from Clifford Geertz's Perspective in Madura - Susantin, Jamiliya; Pahlevi, Yusron; Roibin, Roibin; Atnawi, Atnawi; Saputera, Abdur Rahman Adi (Faculty of Law Universitas Trunojoyo Madura, 2026)
This study aims to analyze the Rokat Pandhaba tradition within Madurese society as a local legal system, employing Clifford Geertz’s interpretive-anthropological approach. It specifically explores the tradition’s normative dimensions, enforcement mechanisms, and its interaction with legal pluralism in Indonesia. The study offers a theoretical contribution by expanding the understanding of Indonesian customary law through Geertz’s thick description, as well as a practical contribution in the form of policy recommendations for the recognition of local legal systems within the framework of national legal pluralism. The research adopts a qualitative methodology using a legal ethnographic approach within an interpretive paradigm. Data were collected through participant observation, in-depth interviews, and documentation across several regions of Madura and analyzed using the thick description method. The findings reveal that Rokat Pandhaba functions as a local legal system characterized by normative elements (customary obligations), sanction mechanisms (both social and supernatural), and a structure of communal authority. This tradition regulates relationships among families, communities, and the spiritual realm, while simultaneously maintaining social order and collective solidarity. Rokat Pandhaba represents a form of living law that dynamically interacts with Islamic law and state law. Accordingly, this study recommends the formal recognition of local legal systems within national legal policy to strengthen an inclusive, context-sensitive model of legal pluralism.